Filles de Caliban : les héroïnes nigérianes de Chimamanda Ngozi Adichie - Marie-Jeanne Gauffre (Caliban: French Journal of English Studies)
Over fifty years after the first African countries became independent, Shakespeare's Caliban, hailed among the colonized as the embodiment of resistance, is still alive in West African literature, addressing the issue of what comes after great struggles, exposing the precariousness of all victories over oppression, and questioning the grand narrative of decolonization. The characters of Nigerian-born Chimamanda Ngozi Adichie, most of them women confronted with a world where skin colour is still a discriminating factor, thus testify to the lingering legacy of colonialism and to their own strategies of self-affirmation. In this paper I will look into a few embodiments of Caliban's uncompromising spirit in her narratives, then scrutinize some persisting after-effects of colonial discourse and finally try to show how she highlights the ineffectiveness of the binary oppositions underlying colonial discourse, and describes forms of human relations more complex than the master-slave dialectic typical of colonial societies.